Analyzing the factors influencing the vulnerability of critical infrastructure in coastal areas : a case study of Thailand - Nonthakarn Benjachat; Pal, Indrajit; Sarawut Ninsawat; Ahmad, Mokbul Morshed; Ministry of Public Works; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
Chonburi and Rayong have been exposed to coastal hazards, with higher intensity and frequency, virtue of its geo-physical location. However, being the heart of Asia in terms of logistics systems and comprehensive transportation, road infrastructure, seaport infrastructure, and healthcare infrastructure led to increased investment in the provinces as known as the Eastern Economic Corridor (EEC). Therefore, analyzing the vulnerability of those critical coastal infrastructures was needed. Mixed method research combines qualitative and quantitative research with a deep understanding and confirmation, allowing one to see that those infrastructures are more vulnerable for various factors. A result of the content analysis showed that Chonburi and Rayong were predicted to be more vulnerable in the future to coastal flooding and erosion, which was distributed along the coast. Roads, seaports, hospitals, and health centers tended to be damaged by the hazards. Furthermore, urbanization, fast industrial growth, and unwell city planning involved increasing the vulnerability of coastal districts. A vast expansion of those critical infrastructures was forced to be constructed closer to the shoreline which are more vulnerable to coastal hazards. Using GIS and satellite images helped in visualizing the change in the coast and allowed identifying vulnerable zones from coastal erosion. It has been proved that the existing road networks, seaports, and hospitals were influenced by the changes in the coast. Through the intensive interview and analysis, it was anticipated that the shore of Rayong province would be more vulnerable to future coastal erosion than Chonburi due to its location. As a result, coastal management, such as geotextile, gabions or breakwater were recommended to implement urgently in the coastline of Chonburi and Rayong. The vulnerability analysis could help the government and related authorities to take necessary action on policy, planning, and suitable coastal protection.
A Research Study Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science in Disaster Preparedness, Mitigation and Management, School of Environment, Resources and Development-School of Engineering and Technology
Research Studies Project Report (M. Sc.) - Asian Institute of Technology, 2023
Keywords: Infrastructure (Economics) -- Thailand -- Chonburi and Rayong -- Case studies; Roads -- Thailand -- Chonburi and Rayong -- Case studies; Coastal zone management -- Thailand -- Chonburi and Rayong